CD146 defines commitment of cultured annulus fibrosus cells to express a contractile phenotype. Issue 8 (8th August 2016) - Nakai, Tomoko; Sakai, Daisuke; Nakamura, Yoshihiko; Nukaga, Tadashi; Grad, Sibylle; Li, Zhen; Alini, Mauro; Chan, Danny; Masuda, Koichi; Ando, Kiyoshi; Mochida, Joji; Watanabe, Masahiko
ABSTRACT: Characterization of cells is important for facilitating cell‐based therapies for degenerative diseases of intervertebral discs. For this purpose, we analyzed mouse annulus fibrosus cells by flowcytometory to detect phenotypic change in their primary cultures. After examination of sixteen cell surface proteins, we focused on CD146 that solely increased during culture expansion. CD146 is known to be a marker for mesenchymal stem cells and for their vascular smooth muscle commitment with expression of contractile phenotype enhanced by SM22α. We sorted CD146+ cells to elucidate their characteristics and the key factors that play a role in this change. Whole cell cultures showed the ability for tripotent differentiation toward mesenchymal lineages, whereas sorted CD146+ cells did not. Expression of CD146 was elevated by addition of transforming growth factor β1, and sorted CD146+ cells expressed higher levels of mRNA for SM22α and Elastin than did CD146− cells. Morphologically, CD146+ cells more broadly deposited extracellular type I collagen than CD146− cells and showed filamentous actin bundles traversing their cytoplasm and cell–cell junctions. Moreover, CD146+ cells demonstrated significantly higher gel contraction properties than CD146− cells when they were embedded in collagen gels. Human annulus fibrosus CD146+ cells also showed higher contractility. Immunohistochemistry determined CD146+ cells localized to the outermost annulus layers of mouse intervertebral disc tissue with co‐expression of SM22α. These results suggest that increment of CD146 expression indicates gradual change of cultured annulus fibrosus cells to express a contractile phenotype and that transforming growth factor β1 enhances this cellular commitment. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1361–1372, 2016.